Improving of technical characteristics of launch vehicles with liquid rocket engines using active onboard de-orbiting systems. (September 2017) - Trushlyakov, V.; Shatrov, Ya.
Abstract: In this paper, the analysis of technical requirements (TR) for the development of modern space launch vehicles (LV) with main liquid rocket engines (LRE) is fulfilled in relation to the anthropogenic impact decreasing. Factual technical characteristics on the example of a promising type of rocket "Soyuz-2.1.v." are analyzed. Meeting the TR in relation to anthropogenic impact decrease based on the conventional design approach and the content of the onboard system does not prove to be efficient and leads to depreciation of the initial technical characteristics obtained at the first design stage if these requirements are not included. In this concern, it is shown that the implementation of additional active onboard de-orbiting system (AODS) of worked-off stages (WS) into the onboard LV stages systems allows to meet the TR related to the LV environmental characteristics, including fire-explosion safety. In some cases, the orbital payload mass increases. Highlights: Requirements for launch vehicles is carry of anthropogenic impact decreasing. The active on-board deorbiting system of stage of launch vehicle is installed. A significant reduction in the anthropogenic impact on the environment is shown. In some cases, the technical characteristics of the launch vehicle are improving.